Lost Libraries
XIII, 294 p.
Keywords: This pioneering volume of essays explores the destruction of great libraries since ancient times and examines the intellectual, political and cultural consequences of loss. Fourteen original contributions, introduced by a major re-evaluative history of lost libraries, offer the first ever comparative discussion of the greatest catastrophes in book history from Mesopotamia and Alexandria to the dispersal of monastic and monarchical book collections, the Nazi destruction of Jewish libraries, and the recent horrifying pillage and burning of books in Tibet, Bosnia and Iraq.